ABUNDANCE INDEX AND COMMUNITY STRUCTURE OF PHYTOPLANKTON IN THE INTEGRATED MARINE AQUACULTURE AREA OF EKAS BAY, WEST NUSA TENGGARA - Yuliana Asri; Nunik Cokrowati; Muhammad Sumsanto; Damai Diniariwisan; Septiana Dwiyanti; Wastu Ayu Diamahesa (Universitas Mataram, 2024)
The development of Ekas Bay as a center for integrated aquaculture activities, particularly through the Floating Net Cage (FNC) system, can impact phytoplankton abundance and water fertility. Phytoplankton, a type of plankton capable of photosynthesis, acts as a primary producer and serves as a key food source for fish and lobsters. The presence of phytoplankton is closely related to the fertility levels of waters designated for marine aquaculture. This study aims to determine the composition and abundance of phytoplankton in the waters of Ekas Bay. The research employed purposive sampling, collecting phytoplankton samples from five predetermined stations: three points near FNCs and two points distant from the FNC area. The results indicate that the plankton abundance in the waters of Ekas Bay is categorized as mesotrophic. The highest phytoplankton abundance was recorded at Station V with 9,523 cells/L, while the lowest was at Station II with 2,150 cells/L. Based on station characteristics, Station V is the farthest point from FNCs, whereas Station II contains a high concentration of FNCs. The community structure, as indicated by the H’, E, and D values, suggests that the waters of Ekas Bay remain in a stable condition. Phytoplankton from the class Bacillariophyta was the most commonly found, although no specific genus was dominant.